Metacognitive Awareness and Listening Proficiency: A Correlational Study of Vocational School Students in Cimahi - Fikri, Fakhri; Irawan, Bambang (Ma'soem University, 2025)
Listening is a complex mental process involving an individual's psychological state and is considered one of the most challenging language skills to acquire. Although several studies have shown a significant positive correlation between metacognitive awareness and listening proficiency, limited research has specifically addressed this issue in the context of Indonesian vocational high schools. To address this gap, the present study aimed to investigate the correlation between metacognitive awareness and listening proficiency among vocational high school students in Cimahi. This research employed a correlational method with 42 students selected through convenience sampling. The Metacognitive Awareness Listening Questionnaire (MALQ) was used to measure students’ metacognitive awareness, while standardized TOEFL scores were used to assess their listening proficiency. Data were analyzed using Spearman’s Rank Correlation Coefficient, as the normality test showed that the data were not normally distributed (p < 0.05). The results indicated a significant correlation (sig. 2-tailed = 0.01; r = 0.500), which falls into the category of moderately strong correlation. Therefore, the null hypothesis was rejected, confirming a significant relationship between metacognitive awareness and listening proficiency among vocational high school students. The findings imply that integrating metacognitive awareness into EFL listening instruction may serve as a valuable strategy to enhance listening proficiency in vocational school settings.